An athlete`s note on the IOC consensus statement on relative energy deficiency in sport: the need for coach education - Douglas, S. (British Journal of Sports Medicine, 2025)
In 2023, the International Olympic Committee (IOC) released their updated consensus statement on relative energy deficiency in sport (REDs), a clinical condition underpinned by exposure to problematic low-energy availability. Low-energy availability results from an unintentional or intentional mismatch of energy expenditure and intake with several aetiologies, including disordered eating, which can range from dieting to pathogenic weight loss methods, potentially leading to an eating disorder.